Roma and Bureaucrats: A Field Experiment in the Czech Republic - Štěpán Mikula; Josef Montag (Masaryk University, Faculty of Economics and Administration, 2022)
This paper tests for discriminatory treatment of the Roma minority by public officials in the Czech Republic. Our focus is on public servants at local job centers whose job is to advise unemployed individuals and process applications for unemployment benefit. Our experimental design facilitates testing for the presence of each of two key (but intertwined) drivers of discrimination: ethnic animus and socioeconomic status prejudice. We find substantial evidence for the presence of discrimination based on both of these sources. Since Roma tend to have lower socioeconomic status, the two sources of discrimination compound for them.
Keywords: J15; D73; H55; 330; Discrimination; Roma; ethnicity; socioeconomic status; public services; social security; field experiment.